Maternity protection in SMEs: an international review - Lewis, Suzan; Stumbitz, Bianca; Miles, Lilian; Rouse, Julia (Geneva, 2014)
"Although rarely quantified, the cost of maternity protection in SMEs is widely perceived to be greater than the benefits and to lead to competitive disadvantage. This review suggests that effective maternity protection is not only feasible in SMEs but can offer a range of positive productivity-related outcomes for enterprises. To achieve these positive effects, and for maternity, paternity and family responsibilities to become “a normal fact of business life”, maternity protection and other work-family balance measures need to fit into the practices and interests of SMEs. The report proposes a multi-pronged approach, involving strategies adopted at state, market, community and family levels to combat gender inequality, support SMEs and ultimately achieve wider development objectives."